Light collection study in scintillation strips with wave length shifting light guide - Senchyshin, V.G.; Adadurov, A.F.; Melnichuk, S.V. (Functional Materials, 2004)
The light collection process in a long polystyrene scintillator strip to a longitudinally placed wavelength shifting light guide is considered. By means of Monte Carlo method, the dependence of light yield on strip parameters: dimensions, bulk attenuation length (BAL), diffuse reflection coefficient have been calculated. The optimum number of light guides and their dimensions are estimated. The results are compared to theoretical estimations within the integrating sphere model. It is shown that in spite of the small strip transverse dimensions, the light yield depends substantially on the material transparency and attains its maximum value at BAL of about 1 m. Рассмотрен процесс светособирания в длинном полистирольном сцинтилляционном стрипе на продольно размещенный спектросмещающий световод. Методом Монте Карло рассчитана зависимость светового выхода от параметров стрипа: его размеров, объемной длины ослабления света (BAL), коэффициента диффузного отражения. Получены оценки оптимального числа световодов и их размеров. Результаты сравниваются с теоретическими оценками в модели светомерного шара. Показано, что несмотря на малые поперечные размеры стрипа, световой выход существенно зависит от прозрачности материала и достигает максимального значения при BAL ~ 1 м. Розглянуто процес свгглозбирання у довгому полістирольному сцинтиляційному стрипі на поздовжньо розташований спектрозміщуючий світловод. Методом Монте Карло обчислено залежність світлового виходу від параметрів стрипу: його розмірів, об’ємної довжини послаблення світла (BAL), коефіцієнта дифузного відбиття. Отримано оцінки оптимальної кількості світловодів та їхніх розмірів. Результати порівнюються з теоретичними оцінками у моделі світломірної кулі. Показано, що незважаючи на малі поперечні розміри стрипу, світловий вихід суттєво залежить від прозорості матеріалу і досягає максимального значення при BAL ~ 1 м.